Patterns of local residual disease and local failure after intensity modulated/image guided radiation therapy for sinonasal tumors in dogs. (4th March 2021) - Poirier, Valerie J.; Koh, Ethel S. Y.; Darko, Johnson; Fleck, Andre; Pinard, Christopher; Vail, David M.
Abstract: Background: Most dogs with sinonasal tumors (SNT) treated with radiation therapy (RT) died because of local disease progression. Hypothesis/Objectives: Our hypothesis is that the majority of local failure and residual disease would occur within the radiation field. Animals: Twenty‐two dogs with SNT treated with RT. Methods: Retrospective cohort study. Inclusion criteria: dogs with SNT receiving 10 daily fractions of 4.2 Gy with intensity modulated radiation therapy (IMRT)/image guided radiation therapy (IGRT) and follow‐up cone beam computed tomography (CBCT). Each CBCT was registered with the original radiation planning CT and the gross tumor volume (GTV) contoured. The GTV was classified as residual (GTVr) or a failure (GTVf). The dose statistic for each GTV was calculated with the original IMRT plan. For GTVf, failures were classified as "in‐field, " "marginal, " or "out‐field" if at least 95, 20‐95, or less than 20% of the volume of failure was within 95% (D95) of the total prescription dose, respectively. Results: There were 52 follow‐up CBCT/CTs. Overall there was a GTVr for 20 dogs and GTVf for 16 dogs. The majority of GTVr volume was within the original GTV. GTVf analysis showed that 75% (12/16) were "in‐field, " 19% (3/16) were "marginal" and 6% (1/16) were "out‐field." Conclusion and Clinical Importance: In‐field failures are the main pattern for local recurrence, and there is evidence of radioresistant subvolumes within the GTV.